Microstructure degradation of service-exposed turbine blades made of directionally solidified DZ125 superalloy - Xie, Yadan; Zhao, Jianjiang; Wang, Jiangwei; Wei, Hua (Frontiers in Materials, 2022)
The investigation about the degradation behavior of turbine blades exposed to complex and extreme environments for long-term in service is of great importance to assess the remaining life of the blades. In our work, the microstructure at different locations of the service-exposed turbine blade was characterized from the micron scale to the nanoscale. The results showed that there are noticeable differences in the microstructure at different locations of the blade and the blade has a complex service history. These conclusions suggest that the most severely damaged part of the blade should be responsible for assessing the remaining life of the blade, moreover, the mechanical properties of materials should not be limited to life at constant temperature and stress, rather non-isothermal and variable stress tests are more instructive in assessing the performance or life of aircraft engine blade materials.